Understanding the Impact of Green Packaging on the Purchasing Intention - Puwianti, Lily; Anita, Anita; Nurjanah, Listia (Jurnal Ilmu Manajemen Advantage, 2025)
The growing environmental awareness has driven companies to adopt eco-friendly packaging as an innovation that minimizes impact and enhances corporate image among sustainability-conscious consumers. This study aims to examine the influence of green packaging on green purchase intention by incorporating four mediating variables: perceived green value, green attitude, green image, and risk perception. A quantitative causal-associative approach was employed, using a judgment sampling technique with 385 respondents residing in Batam. Data were collected through questionnaires and analyzed using appropriate statistical methods. The results indicate that green packaging significantly affects all mediating variables. Furthermore, perceived green value, green attitude, and green image positively influence green purchase intention, whereas risk perception negatively influences it. These findings provide valuable insights for businesses in developing more effective green marketing strategies, particularly by accounting for the generational characteristics of their consumer segments.